2016
DOI: 10.1136/jim-2016-000111
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mmp2-1306C/T and Timp2G-418C Polymorphisms with Relapsing Remitting Multiple Sclerosis

Abstract: In the RRMS group, the genotype and allele frequencies of MMP2-1306C/T polymorphism showed significant differences from the controls. These results indicate that MMP2 might play a role in the pathogenesis of MS even during the inflammation stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Prion proteins have been implicated in myelin diseases, as proteolysis of prion proteins is beneficial for myelin sheath maintenance . Polymorphisms of metalloproteinase inhibitor 2 have been mentioned in CSF of relapsing remitting …”
Section: Discussionmentioning
confidence: 99%
“…Prion proteins have been implicated in myelin diseases, as proteolysis of prion proteins is beneficial for myelin sheath maintenance . Polymorphisms of metalloproteinase inhibitor 2 have been mentioned in CSF of relapsing remitting …”
Section: Discussionmentioning
confidence: 99%
“…TIMP‐2, the main endogenous inhibitor of MMP‐2, is responsible for regulating the functions of MMPs . The MMP‐2/TIMP‐2 expression ratio is an important factor in certain nervous and vascular disorders . In our study, the TIMP‐2 (rs2277698) gene polymorphism was shown to be weakly associated with DAVF patients subgrouped by CVR grading ( P = 0.026; OR 3.0 [95% CI 1.1–8.2]).…”
Section: Discussionmentioning
confidence: 53%
“…MMP-2 has been detected in microglial nodules and microglial-like cells, where it contributes to inflammation, and is implicated in further break down of myelin basic protein (MBP) and oligodendrocyte death [ 43 ], and destabilizes the BBB [ 44 , 45 ]. Aksoy et al analyzed the MMP-2 (-1306) gene polymorphism in patients with relapsing remitting MS, and found statistically significant differences in the frequency of CT and TT genotypes and T allele in comparing patients with relapsing remitting MS to control subjects [ 46 ]. Meanwhile, in our study, differences in the genotype and allele distribution did not show any statistical significance between ON with MS and control groups.…”
Section: Discussionmentioning
confidence: 99%